PENGARUH STRATEGI PEMASARAN, KEPEMIMPINAN, RISIKO SUKU BUNGA TERHADAP KINERJA KEUANGAN KOPERASI SIMPAN PINJAM - Sari, Agnes Kartika Mutiara; Ridaryanto, Petrus (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2023)
The purpose of this study is to examine the effect of marketing strategy, leadership and interest rate risk on the financial performance of Credit Union. The sample of this study is 44 Credit Union members of the Credit Union Central of Jakarta. The author conducted a questionnaire survey to collect data and test the hypotheses developed in this study. the author sent the questionnaires to the boards and managers of Credit Union. Regression analysis of multiple linear was applied to analyze the data. The results show that leadership has a positive and significant effect on the financial performance of Credit Union. Marketing strategy and interest rate risk have no effect on the financial performance of Credit Union.The results of this study can be used as consideration for the Credit Union to improve skills leadership of the boards and managers.The study has three limitation. First the authors collect data from Credit Union to minimize the effect of data heterogeneity. To improve the generalizability of the study, future study might consider using data from other types of cooperatives. Second, this study uses primary data so it has risks respondent subjectivity, future study might use different ways of measuring interest rate risk using more objective empirical proxies such as income gap